Derechos Humanos - España VS Colombia (2014)
This article seeks to compare Human Rights in Colombia, with Human Rights in Spain. For this we will make a brief historical review of human rights in each country and throughout history. It also aims to make different comparisons from which to judge the implementation of Human Rights in the two nanciones